Acceleration of protons and deuterons up to 35 MeV and generation of 1013 neutrons in a megaampere deuterium gas-puff z-pinch - Klir D. Daniel; Shishlov A. V. Aleksandr Viktorovich; Kokshenev V. A. Vladimir Alekseevich; Kubes P. Pavel; Rezac K. Karel; Dudkin G. N. Gennadiy Nikolaevich; Padalko V. N. Vladimir Nikolaevich; Ratakhin N. A. Nikolay Aleksandrovich; Varlachev V. A. Valery Aleksandrovich (2019, 2019)
Title screen